2020
DOI: 10.1007/s11239-020-02160-1
|View full text |Cite|
|
Sign up to set email alerts
|

Acute pulmonary embolism in COVID-19 related hypercoagulability

Abstract: Since December 2019, a novel Coronavirus (SARS-CoV-2) was confirmed as the etiologic agent of a worldwide outbreak of a pneumonia that can result in severe respiratory failure. This clinical entity seems to be associated with a marked hypercoagulable state that causes both arterial and venous thromboembolic complications. Therefore, an adequate anti-thrombotic prophylaxis is recommended in hospitalized COVID-19 patients. Although rapidly worsening respiratory symptoms in a patient with SARS-CoV-2 respiratory i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 10 publications
0
22
0
5
Order By: Relevance
“…Several studies have reported the increased prevalence of thromboembolic events in COVID-19 infection. [8][9][10] The Figure 1 Initial anteroposterior (AP) chest radiograph depicting a large right-sided pneumothorax. Note the considerable leftward mediastinal shift.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the increased prevalence of thromboembolic events in COVID-19 infection. [8][9][10] The Figure 1 Initial anteroposterior (AP) chest radiograph depicting a large right-sided pneumothorax. Note the considerable leftward mediastinal shift.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the increased prevalence of thromboembolic events in COVID-19 infection. 8–10 The systemic inflammation associated with COVID-19 and endothelial dysfunction, along with the generated hypercoagulable state, are the likely contributory factors to the pathogenesis of acute pulmonary emboli. The viscosity of blood is further increased by the hypoxia from severe pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Геморрагическое пропитывание легочной ткани нередко является предвестником развивающегося острого респираторного дистресс-синдрома. Именно в развитии ге-моррагического отека ряд авторов видят причину исключительно быстрой отрицательной динамики изменений в легких при изначально небольшой площади поражения [21][22][23][24].…”
Section: рентгеноморфологические сопоставленияunclassified
“…2). Наиболее часто они относятся к криптогенной ОП, а также к ОП известной природы: при лекарственных поражениях, других, в т. ч. вирусных, инфекциях, радиационных повреждениях, системных заболеваниях соединительной ткани [24][25][26][27]. Типичными визуальными признаками являются многочисленные рассеянные (patchy) участки уплотнения легочной ткани по типу «матового стекла» в сочетании с консолидацией.…”
Section: рентгеноморфологические сопоставленияunclassified
See 1 more Smart Citation